Memory Reconsolidation Mediates the Updating of Hippocampal Memory Content - Lee, Jonathan L. (Frontiers in Behavioral Neuroscience, 2010)
The retrieval or reactivation of a memory places it into a labile state, requiring a process of reconsolidation to restabilize it. This retrieval-induced plasticity is a potential mechanism for the modification of the existing memory. Following previous data supportive of a functional role for memory reconsolidation in the modification of memory strength, here I show that hippocampal memory reconsolidation also supports the updating of contextual memory content. Using a procedure that separates the learning of pure context from footshock-motivated contextual fear learning, I demonstrate doubly dissociable hippocampal mechanisms of initial context learning and subsequent updating of the neutral contextual representation to incorporate the footshock. Contextual memory consolidation was dependent upon BDNF expression in the dorsal hippocampus, whereas the footshock modification of the contextual representation required the expression of Zif268. These mechanisms match those previously shown to be selectively involved in hippocampal memory consolidation and reconsolidation, respectively. Moreover, memory reactivation is a necessary step in modifying memory content, as inhibition of hippocampal synaptic protein degradation also prevented the footshock-mediated memory modification. Finally, dorsal hippocampal knockdown of Zif268 impaired the reconsolidation of the pure contextual memory only under conditions of weak context memory training, as well as failing to disrupt contextual freezing when a strong contextual fear memory is reactivated by further conditioning. Therefore, an adaptive function of the reactivation and reconsolidation process is to enable the updating of memory content.